Structural Fragments Izopolivolframat–Anions and Gibbs Energy of Formation - Rozantsev, G.M. (Physics and Chemistry of Solid State, 2015)
The method of mathematical modeling (program CLINP 2.1, Newton's method) on the basis of the pH-potentiometric titration data allowed to calculate concentration constants of isopolytungstate anions (IPTA) formation at different ionic forces (I = 0,01 ‑ 0,5 M). Thermodynamic constants of IPTA formation were obtained as a result of processing by Pitzer method using the concentration constans. The standard Gibbs energy of isopolytungstate anions formation were calculated. The last ones allowed to estimate the thermodynamic probability of the reactions, that can be used in the synthesis of salts containing these anions. The structure of known isopolytungstates can be built from the combination of such fragments: WO, W2O, W3O, W4O and W5O. The calculation of standard Gibbs energy of these fragments formation allowed to characterize the structure of hexatungstate-anion W6O20(OH)26-, which does not contain three terminal oxygen atoms. Such approach of using Gibbs energy of building blocks was recommended for prediction of equilibrium constants values in the mathematical modeling.